Crisis Handling and Conflict Resolution in Papuan and Local Communities in Demonstration Cases Commemorating the 2019 New York Agreement - Habibi Za’idatul Ma’muriyah; Maulina Pia Wulandari; Bambang Dwi Prasetyo (Global Writing Academica Researching & Publishing, 2022)
Conflicts and crises are situations that cannot be predicted, can come at any time, and cannot be avoided, so crises management actions and conflict resolution are needed from demonstration conflicts to commemorate the New York Agreement in August 2019 in Malang City. The situation that occurs is a government crisis situation that requires conflict resolution and crisis management by Malang City so that crises and conflicts can be muted so that they do not continue. The research to see how Malang City handles this crisis and conflict resolution uses a constructivist paradigm with a qualitative research type. This study aims to find strategies to reduce crises and reduce ongoing conflicts. The method of data collection carried out in this study was an interview with the Public Relations of Malang City Government, supported by data collection, which was carried out through documentation. The Apologia theory and the conflict theory used in this study show that Malang City uses the deny strategy, conciliation strategy, transcendence strategy, and bolstering strategy. Malang City Government also conducts negotiations and acts with the Papuan people who live in Malang, so the strategies used are conflict resolution and crisis management strategies that produce win-win solutions so that conflicts are reduced and not prolonged.